1999
DOI: 10.1007/s003830050544
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mucin on bacterial translocation in I-407 fetal and Caco-2 adult enterocyte cultured cell lines

Abstract: Although the intestinal mucosa forms a crucial barrier between the host and the environment, bacterial translocation (BT) occurs frequently in neonates and may be a source of sepsis. The intestinal mucous gel layer is thought to be a vital component of the gut barrier and is composed, in part, of a family of glycoproteins known as mucins. Our aim was to study the effects of mucin on BT in an enterocyte cell-culture model using a fetal (I-407) and an adult (Caco-2) intestinal cell line. I-407 and Caco-2 cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…MUC2 also plays a critical role in mucosal protection by preventing bacterial pathogens from gaining access to the epithelium. Indeed, the protective effect of probiotics on bacterial translocation is associated with MUC2 over expression (39), and the application of mucins to the surface of neonatal epithelial cell line was shown to inhibit bacterial translocation (40). In patients with Hirschsprung's disease, a decrease in the expression of MUC2 has been linked to the development of associated enterocolitis (15).…”
Section: Discussionmentioning
confidence: 99%
“…MUC2 also plays a critical role in mucosal protection by preventing bacterial pathogens from gaining access to the epithelium. Indeed, the protective effect of probiotics on bacterial translocation is associated with MUC2 over expression (39), and the application of mucins to the surface of neonatal epithelial cell line was shown to inhibit bacterial translocation (40). In patients with Hirschsprung's disease, a decrease in the expression of MUC2 has been linked to the development of associated enterocolitis (15).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, those patients who developed HAEC had mucin turnover rates that were seven times lower than those without enterocolitis [35]. Gork et al [36] showed mucin-inhibited bacterial translocation in vitro across both foetal and adult-cultured intact enterocyte monolayers. Also in this study, they demonstrated that the inhibitory effect on translocation was lower on the foetal cells compared to the adult cells.…”
Section: Mucinmentioning
confidence: 97%
“…A major physical barrier of the gut is the thick mucin-rich glycocalyx that lines the entire alimentary canal (12). In the intestine and colon, the epithelial monolayer is 93%-95% absorptive enterocytes (13), whose surface area is further increased by microvilli on apical surfaces.…”
Section: Intestinal Mucosamentioning
confidence: 99%
“…The amount of lysozyme in human milk varies, but is often approximately 100 g/L and is found in the feces of breast-fed infants (68), indicating that it survives intestinal digestion sufficiently to potentially break down the more vulnerable cell walls of Gram-negative bacteria. Haptocorrin, a human milk protein that chelates vitamin B 12 , is resistant to digestion and inhibits enterotoxigenic E. coli.…”
Section: Human Milkmentioning
confidence: 99%